2017
DOI: 10.5194/esurf-2017-68
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of the Askja caldera July 2014 landslide, Iceland, from seismic signal analysis: precursor, motion and aftermath

Abstract: Abstract. Using data from a network of 58 seismic stations, we characterise a large landslide that occurred at the southeastern corner of the Askja caldera, Iceland, on 21 July 2014, including its precursory tremor and mass wasting aftermath. Our study is motivated by the need for deeper generic understanding of the processes operating not only at the time of catastrophic slope failure, but also in the preparatory phase and during the transient into the subsequent stable state.In addition, it is prompted by th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…The seismic signals generated by the granular column collapses have an emergent rise and long decay (Figures b, b, and b) and compare well with seismic signals of landslides and rockfalls observed in the field (Dammeier et al, ; Hibert et al, , ; Moretti et al, ; Pérez‐Guillén et al,; Schneider et al, ; Schöpa et al, ). Similarly, as was previously reported by Farin et al (), on an horizontal slope, the shape of the seismic envelope is symmetrical with respect to its maximum.…”
Section: Comparison Of the Seismic And Dynamic Parameterssupporting
confidence: 72%
See 2 more Smart Citations
“…The seismic signals generated by the granular column collapses have an emergent rise and long decay (Figures b, b, and b) and compare well with seismic signals of landslides and rockfalls observed in the field (Dammeier et al, ; Hibert et al, , ; Moretti et al, ; Pérez‐Guillén et al,; Schneider et al, ; Schöpa et al, ). Similarly, as was previously reported by Farin et al (), on an horizontal slope, the shape of the seismic envelope is symmetrical with respect to its maximum.…”
Section: Comparison Of the Seismic And Dynamic Parameterssupporting
confidence: 72%
“…Indeed, the seismic signals of Hibert, Ekström, et al () are recorded far from the flows and seismic signals are in a relatively low frequency range (3‐10 Hz) while particle impacts in the field can generate signals of frequency up to 150 Hz (e.g. Dammeier et al, ; Farin et al, ; Helmstetter & Garambois, ; Hibert et al, ; Hibert, Malet, et al, ; Schöpa et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post‐seismic landslides can form at higher rates during heavy rainfall, possibly driven by clearing of oversteepened slopes in the crowns of EQTLs, vegetation and groundwater changes, and altered mechanical properties of bedrock and regolith (Marc et al, ). Oversteepened slopes in the crowns of coseismic landslides contributed less than half of the total post‐seismic landslide volume in documented cases (Schöpa et al, ). Vegetation and groundwater level changes have time scales that differ from those of the post‐seismic landslide transient (<10 years).…”
Section: Post‐seismic Geological Hazardsmentioning
confidence: 99%
“…Yamada et al (2016a); Poli (2017); Helmstetter et al (2017a) argued that the high correlation between the repetitive events could only be explained by stick-slip movement of the locked section(s), while a cracking process would imply a migration of the location of the events and a change in the events waveforms. Schöpa et al (2017) argued that the presence of gliding frequencies could only be produced by similar shown that the number of events is significantly correlated with rainfall and displacement rates (Amitrano et al, 2005;Helmstetter and Garambois, 2010;Walter et al, 2012;Brückl et al, 2013;Tonnellier et al, 2013;Vouillamoz et al, 2017) although some increases of seismicity rates are not correlated to any surface displacement (Helmstetter and Garambois, 2010;Walter et al, 2012;Tonnellier et al, 2013;Vouillamoz et al, 2017 the slow motion and fast acceleration toward failure of unstable slopes. Moreover, the condition of occurrence of precursory seismic events during the nucleation phase of the landslide failure must be also better understand.…”
Section: Discussionmentioning
confidence: 99%